Tajikistan Economic Update, Fall 2015 : A Moderate Slowdown in Economic Growth Coupled with a Sharp Decline in Household Purchasing Power - World Bank Group (World Bank, Washington, DC, 2015)
Tajikistan’s economy exceeded expectations during the first six months of 2015 despite a challenging external environment. According to official data, GDP growth slowed only moderately from 6.7 percent in the first half of 2014 to 6.4 percent year on year (y/y) in the first half of 2015, even as remittances from Russia fell, global demand weakened, and prices for the country’s key export commodities such as aluminum and cotton dropped significantly. Domestic factors continued to drive growth, and both the construction and industrial sectors expanded as the economy’s focus shifted from consumption to investment. The state budget surplus reached 1 percent of GDP, and the external public debt to GDP ratio dropped to below 20 percent. The sharp decline in remittances is limiting the growth of household consumption and could threaten the sustainability of recent gains in poverty reduction and shared prosperity. According to the National Bank of Tajikistan (NBT), remittances dropped by 32 percent (y/y), in US dollar terms during the first six months of 2015. Although the decline was less dramatic (about 18 percent) in Tajikistan somoni (TJS) terms, income losses were much larger than implied by GDP statistics. Falling remittances, limited employment creation outside the public sector, and rising prices are slowing the rate of poverty reduction. Moreover, the lack of well-targeted social programs leaves households vulnerable to economic shocks.